2009
DOI: 10.3748/wjg.15.2151
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of β-adrenergic blocker plus 5-isosorbide mononitrate and endoscopic band ligation for prophylaxis of esophageal variceal rebleeding: A meta-analysis

Abstract: AIM:To systematically assess the efficacy and safety of β-adrenergic blocker plus 5-isosorbide mononitrate (BB + ISMN) and endoscopic band ligation (EBL) on prophylaxis of esophageal variceal rebleeding. METHODS:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
1
16
1
1
Order By: Relevance
“…It should also be taken into account that a large proportion of deaths are not related to rebleeding but to other complications of portal hypertension or liver dysfunction . Both liver function and portal hypertension are not affected by therapies that act locally on varices but are not pathophysiologically oriented, such as EVL . Accordingly, an improvement in mortality may occur more likely with therapies that improve portal hypertension .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be taken into account that a large proportion of deaths are not related to rebleeding but to other complications of portal hypertension or liver dysfunction . Both liver function and portal hypertension are not affected by therapies that act locally on varices but are not pathophysiologically oriented, such as EVL . Accordingly, an improvement in mortality may occur more likely with therapies that improve portal hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…This combined drug therapy has been shown to be superior to β‐blockers alone and to EST . Meta‐analyses of trials comparing β‐blockers + ISMN with EVL have shown no significant differences in rebleeding or survival . A recent study suggests an improvement in survival favouring combined drug therapy over EVL in the long‐term follow‐up .…”
mentioning
confidence: 99%
“…Other randomized trials on IsMn vs. beta‐blockers or IsMn plus beta‐blockers vs. beta‐blockers or endoscopic therapy have reached equivocal results 9, 10 . Recent meta‐analyses including between four and 25 randomized trials have found that the combination of endoscopic and pharmacological therapy with beta‐blockers alone or combined with IsMn may be more effective in reducing the risk of rebleeding than either of the therapeutic options used alone 11–13 . No clear effect on mortality was identified.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, this treatment has a high recurrence rate, also needs advanced technique and incurs high cost. 20,21 Endoscopic variceal band ligation is mostly performed in the in-patient setting and is effective inprimary and secondary prophylaxis of bleeding esophageal varices in patients with cirrhosis. 18 Our study was a single centered descriptive observational study in which EVL therapy after pre-endoscopic preparation of the patients and confirmation of esophageal varices was done to see the required numbers of sessions to obliterate the esophageal varices in LC patients.…”
Section: Discussionmentioning
confidence: 99%